#### Answer

(1, -2)

#### Work Step by Step

Rewrite 3x + y =1 as y = 1 - 3x. Plug this into 5x + 2y = 1
5x + 2(1 - 3x) = 1
5x + 2 - 6x = 1
-x = -1
x = 1
Plug x =1 back into y = 1 - 3x
y = 1 - 3(1) = -2
Solution is (1, -2)

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

(1, -2)

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.